Valoración de inventario en cumplimiento de la sesión No. 13 para la razonabilidad contable de empresas con actividad de comercio - Toro Espinoza, Mayra Yadira (2015)
This research work has as main objective to present a proposañ to improve the level of service to the customer as well as the registration procedures of inventory in trading activity in the implementation of International Financial Reporting Standards for SMEs Section Nº 13, identifying its main causes lack of improper registration of existing goods in inventory, for which various methods were evaluated and determined that the weighted average method was best suited for the use of the accounting processes, effective for the entry and exit of the product from their cellars staff provinding facilities for effective monitoring and control of their inventory and thus significantly improving profitability, knowing that inventory valuation it is important in the management and supply of goods, the project leads to the conclusion that it is possible for companies to adapt to the IFRS for SMEs, making a favorable market response. The main conclusion to be drawn is to enhance the merchandise in accordance with International Financial Reporting Standards for SMEs,Section 13. The study reveals the theoretical and posible effectiveness of the practice of the methods used for making decisions in the registration and valuation of inventories.